Spatial ICT Clusters in Sweden - An Empirical Method to Identify a Necessary Condition for Existence - Charlie Karlsson (European Regional Science Association (ERSA), 2003)
The tendency of information and communication technology (ICT) industries to cluster spatially is well documented in the international literature. Sweden has been characterised of a rapid growth of most ICT industries during the 1990s. In this paper we examine the spatial clustering of ICT industries in Swedish functional regions and changes in the patterns of clustering during the period 1990-2001. To be defined as a region with an ICT cluster a region must exhibit a significant overrepresentation of both ICT plants and ICT employment given its size in terms of population. By using this method it is possible to identify macro, meso and micro clusters. We examine the life cycles of these clusters during the period 1990-2001 in terms of births, growth, decline and disappearance as well similarities and differences between the different clusters in terms of, for example, industrial composition and regional factor endowments. We also compare the development of the ICT sector in regions with ICT clusters with the development of the ICT sector in regions specialised in large scale ICT production and in regions specialised in small scale ICT entrepreneurship. Based upon the results we also formulate recommendations for ICT policies in different types of regions.
Keywords: 330